The Art of Goodbye: Exploring Health Concerns - Lynda Spence (EDIS)
Issues and questions about care at the end of life are as unique and complex as the individual receiving care. The condition and culture of the patient and family, religion, spirituality, education, occupation, social class, friends, and personal preferences can affect end-of-life care. Sometimes decisions are made by the individual patient. At other times, the family and health care providers are involved. This 6-page fact sheet, which is part of a series entitled The Art of Goodbye: End of Life Education series, explores health concerns and discusses aspects and types of care at the end of life. Written by Lynda Spence, and published by the UF Department of Family, Youth and Community Sciences, October 2016.